Diversity of pili-specific bacteriophages: genome sequence of IncM plasmid-dependent RNA phage M - Rumnieks, Janis; Tars, Kaspars (BMC microbiology, 2012)
Background Bacteriophages of the Leviviridae family are small RNA viruses with linear, positive-sense, single-stranded RNA genomes that encode only four proteins. All phages of this family require bacterial pili to attach to and infect cells. Leviviridae phages utilizing F-pili for this purpose have been extensively studied. RNA phages specific for conjugative plasmid-encoded pili other than that of plasmid F have been isolated, but are much less understood and their relation to the F-pili-specific phages in many cases is not known. Results Phage M has the smallest known Leviviridae genome to date and has the typical genome organization with maturation, coat and replicase genes in the 5′ to 3′ direction. The lysis gene is located in a different position than in other known Leviviridae phages and completely overlaps with the replicase gene in a different reading frame. It encodes a 37 residue long polypeptide that contains a transmembrane helix like the other known lysis proteins of leviviruses. Sequence identities of M proteins to those of other phages do not exceed 25% for maturation protein, 51% for coat protein and 41% for replicase. Similarities in protein sequences and RNA secondary structures at the 3′ untranslated region place phage M together with phages specific for IncP, IncC and IncH, but not IncF plasmid-encoded pili. Phylogenetic analysis using the complete genome sequences and replicase proteins suggests that phage M represents a lineage that branched off early in the course of RNA phage specialization on different conjugative plasmids. Conclusions The genome sequence of phage M shows that it is clearly related to other conjugative pili-specific leviviruses but has an atypical location of the lysis gene. It provides a better view on the remarkable diversification of the plasmid-specific RNA phages.